Epistocracy vs constitutional democracy: A Hayekian response to Jason Brannan - Buğra Kalkan; Pınar Ebe Güzgü (Masyarakat, Kebudayaan dan Politik, 2023)
Jason Brennan, who proposes assessing democratic decisions based on non-procedural expert knowledge from a pure utilitarian standpoint, holds a prominent position among libertarian critiques of democracy. Brennan contends that epistocratic regimes can outperform democracies since democracies perform badly due to the phenomena of rational ignorance and deliberative democratic methods cannot solve this problem. Brennan, who compares epistocratic institutions to constitutional institutions, wants to tame democracies using negative externality arguments. In this study, we demonstrate that constitutional democracies cannot be assessed by the Brennanian metrics and that epistocracy will erode the libertarian political successes of constitutional democracy. Two important arguments back up this conclusion. First, transforming libertarian ideals beyond constitutional rules into the standard for daily politics allows experts tremendous discretion. Even with good intentions, the unchecked discretion of experts would most likely undermine the general, abstract, and egalitarian rules required by a complex society. Second, taking the concept of rational choice out of its original context will make the distinction between constitutional and unconstitutional governments unclear. Therefore, the libertarian ideal of the limited government established by the separation of powers and the procedures of checks and balances would lose its significance, giving place to the unchecked discretion of expert rule.